Plasma Human Cartilage Glycoprotein‐39 and Cognitive Impairment After Acute Ischemic Stroke - Ziyi Wang; Kaixin Zhang; Chongke Zhong; Zhengbao Zhu; Xiaowei Zheng; Pinni Yang; Bizhong Che; Yaling Lu; Yonghong Zhang; Tian Xu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Our study aimed at evaluating the association between plasma human cartilage glycoprotein‐39 (YKL‐40) and cognitive impairment at 3 months among patients with acute ischemic stroke. Methods and Results Plasma YKL‐40 levels were measured in 604 participants from the China Antihypertensive Trial in Acute Ischemic Stroke. Cognitive impairment outcomes were assessed at 3 months poststroke using the Mini‐Mental State Examination and the Montreal Cognitive Assessment. According to the Mini‐Mental State Examination score, patients in the highest quartile of YKL‐40 had a 2.01‐fold (95% CI, 1.23–3.29; P for trend=0.009) risk of poststroke cognitive impairment compared with those in the lowest quartile. Each 1 SD difference of logarithm‐transformed YKL‐40 was associated with a 28% (95% CI, 7–53) increased risk for the outcome. The multiple‐adjusted spline regression model confirmed dose–response relationships between YKL‐40 and poststroke cognitive impairment (P for linearity=0.01). Adding YKL‐40 to a model containing conventional risk factors significantly improved the discriminatory power (area under the receiver operating characteristic curve improved by 0.02, P=0.03). When cognitive impairment was defined using the Montreal Cognitive Assessment score, similar findings were observed. Conclusions Elevated YKL‐40 levels were associated with an increased risk of cognitive impairment at 3 months among patients with acute ischemic stroke. Registration URL: clinicaltrials.gov; Unique Identifier: NCT01840072.